Morphoanatomic aspects and phytochemical screening of Plinia edulis (Vell.) Sobral (Myrtaceae) (Revista Brasileira de Ciências Farmacêuticas, 2008)
Plinia edulis (Myrtaceae), popularly known as "cambucá", is a Brazilian medicinal plant employed in the treatment of stomach problems and throat affections by the "caiçaras", fishermen of coastal localities. Aiming to contribute with the species knowledge the leaves of P. edulis were analyzed macro and microscopically and the chemical composition of the volatile oil was determined using a combination of GC/MS and retention indices. The antimicrobial assay and the phytochemical screening of the aqueous ethanol extract of the leaves have been performed to correlate the secondary metabolites and the traditional use. Leaves present morphological characteristics of others Myrtaceae species and some particularities, such as the circular idioblasts in number of 2 to 4, scattered perpendicularly at the adaxial surface, with druses or prismatic crystals. In the volatile oil fifteen components have been identified, of which epi-α-cadinol (21.7%), α-cadinol (20.2%) and trans-caryophyllene (14.2%) were major. The phytochemical screening of the aqueous ethanol extract showed the presence of substances with pharmacological interest, such as flavonoids, tannins, saponins and terpenoids but, despite of the presence of these classes, the extract did not inhibit the growth of Aspergillus niger, Candida albicans, Escherichia coli and Staphylococcus aureus in a concentration of 1,000 mg/mL.